Truth in Serial Form Serial Formats and the Form of the Series, 1850-1930 - Maskarinec, Malika (PARADIGMS, 2023)
This volume examines the veritable explosion of serialized formats in all of forms representation, from painting to printing throughout the nineteenth century and into the twentieth, and the way in which these formats encouraged experiments with the series form and raised questions of truthfulness.